Novel Estimates of Bird Migration Traffic at the Continental Scale Using Participatory Science Data - Ethan Plunkett; Yuting Deng; David L. Slager; Miguel Fuentes; Yangkang Chen; Benjamin M. Van Doren; Adriaan M. Dokter; Daniel Sheldon (Global Ecology and Biogeography, 2026)
Aim Quantifying movement patterns of migratory birds throughout their annual cycles is critical for effective conservation planning. The BirdFlow project uses eBird participatory science data products to model species‐level migratory trajectories across entire ranges. However, BirdFlow trajectory models are not readily compatible with location‐based monitoring technologies such as weather radar. We develop a scalable, species‐level measurement of nocturnal bird migration traffic and assess its utility for integration with radar monitoring. Innovation We introduce the BirdFlow migration traffic rate (BMTR), a location‐based metric of migratory passage for individual species derived from BirdFlow models. BMTR quantifies the weekly proportion of a species' population passing over a transect, can be calculated across a species' entire range and can be converted to absolute numbers using population estimates. We applied this framework to 312 nocturnal migratory bird species in North America. Aggregating all species' migration activities, we compared them with average weekly nocturnal migration traffic detected by 152 NEXRAD weather surveillance radars over 28 years. We further evaluated the use of BMTR to disaggregate radar‐derived migration traffic into species‐level estimates. Main Conclusions BirdFlow‐ and radar‐derived migration traffic showed strong agreement ( r = 0.784), particularly along the Mississippi and Atlantic Flyways, with models incorporating demographic adjustments performing best. Annual nocturnal migration traffic estimated by BirdFlow and radar was closely aligned, with BirdFlow estimates averaging 33.3% higher. BMTR effectively captured major flyways, high‐traffic routes and seasonal migration dynamics. It also enabled disaggregation of radar traffic into species‐level contributions, revealing dominant species at specific locations. BMTR provides a new methodological bridge between trajectory‐based BirdFlow movement models and location‐based monitoring approaches. It offers a scalable, species‐specific tool for migration ecology and conservation, supports monitoring in areas without radar coverage and enables new opportunities for public engagement through visualisation of near real‐time, species‐level migration.

Structuring the skies: Diel dynamics of migratory animal movement in the lower atmosphere - Silvia Giuntini; Carolyn S. Burt; Annika L. Abbott; Carrie Ann Adams; Maria Carolina T. D. Belotti; Yuting Deng; Miguel F. Jimenez; Jeffrey F. Kelly; Subhransu Maji; Meredith Nash‐Martin; Sam Simon; Daniel Sheldon; et al. (Ecology, 2025)
Earth's lower atmosphere is a vital ecological habitat, home to trillions of organisms that live, forage, and migrate through this medium. Despite its importance, this space is seldom considered a primary habitat for ecological or conservation prioritization, making it one of the least studied environments. However, it plays a crucial role as a global conduit for the transfer of biomass, weather, and inorganic materials. Fundamental research is essential to address core ecological questions related to the ecological consequences of this habitat's intricate spatial and temporal structure. To advance our understanding of airspace use by migratory animals, we analyzed over 108 million 5‐min radar observations from 143 NEXRAD sites, focusing on 24‐h diel cycles across the contiguous United States. This extensive dataset, spanning from 1995 to 2022, allowed us to quantify aerial space use by systematically identifying peak activity times, the portion of the airspace that contained the majority of migration activity, and the percentage of migrants passing across diurnal and nocturnal diel cycles. We found that airspace is used predominantly during nocturnal periods in both spring and autumn (88%), while summer exhibited a more balanced distribution (54% nocturnal). Additionally, the percentage of nocturnal activity increased with latitude in spring and autumn but decreased in summer. Peak aerial activity typically occurred about 4 h after local sunset in both spring and autumn, with variations based on latitude and longitude. During these peak times, on average, half of the aerial movement was confined within a vertical band of 516 meters, starting around 355 m above ground level. Our research underscores the need to view the lower atmosphere as a structured habitat with significant ecological importance.

Assessing the Corn Belt as an anthropogenic barrier to migrating landbirds in the United States - Fengyi Guo; Jeffrey J. Buler; Adriaan M. Dokter; Kyle G. Horton; Emily B. Cohen; Daniel Sheldon; Jaclyn A. Smolinsky; David S. Wilcove (Conservation Biology, 2025)
Migrating landbirds adjust their flight and stopover behaviors to efficiently cross inhospitable geographies, such as the Gulf of Mexico and the Sahara Desert. In addition to these natural barriers, birds may increasingly encounter anthropogenic barriers created by large‐scale changes in land use. One such barrier could be the Corn Belt in the Midwest United States, where 76.4% of precolonial vegetation (forest and grassland combined) has been replaced by agricultural and urban areas, primarily corn fields. We used 5 years of data from 47 weather radar stations in the United States to compare the population‐level flight patterns of migrating landbirds crossing the Corn Belt and the forested landscapes south and north of it in spring and autumn. We also examined the impacts of the Corn Belt relative to the Gulf of Mexico on the stopover behavior of migrating birds by comparing changes in the proportion of migrants that stop to rest (stopover‐to‐passage ratio [SPR]) relative to distance from both barriers. Birds showed increased meridional airspeeds and stronger selection for tailwinds when crossing the Corn Belt compared with forested landscapes. For birds crossing the Gulf of Mexico, the highest proportion of migrants stopped to rest after crossing the Gulf, and SPR decreased sharply as distance from the shoreline increased. We did not find this pattern after migrants crossed the Corn Belt, although the SPR increased in the Corn Belt as birds approached the down‐route forest boundary in both seasons. This weaker pattern for stopover propensity after crossing the Corn Belt is likely due to its narrower width, the availability of small forest patches throughout the Corn Belt, and the subset of species affected, compared with the gulf. We recommend restoring stepping stones of forest in the Corn Belt and protecting woodlands along the Gulf Coast to help landbirds successfully negotiate both barriers.

Continental Connections: Changing Temperature, Wind and Precipitation Advance the Postbreeding Roosting Phenology of Avian Aerial Insectivores - Yuting Deng; Birgen Haest; Maria C. T. D. Belotti; Wenlong Zhao; Gustavo Perez; Elske K. Tielens; Daniel R. Sheldon; Subhransu Maji; Jeffrey F. Kelly; Kyle G. Horton (Global Ecology and Biogeography, 2025)
Aim Migratory birds are under threat by climate change. Successfully conserving them requires knowing which climatic factors drive changes in their migratory behaviour. Weather conditions may directly or indirectly affect the temporally disjointed life history stages of migratory birds, including the breeding, roosting and nonbreeding stages. However, the influences of these broad‐scale patterns are often not studied together. Coupling migratory bird movements estimated using weather radar (NEXRAD) with long‐term and large‐scale environmental data allows us to overcome these spatiotemporal uncertainties. Here, we assess environmental drivers of the phenology of postbreeding roosting of aerial insectivores in the Great Lakes region (USA) by evaluating predictors during the months leading up to roosting across species' ranges. Location Northern United States and Canada. Time Period 21‐year (2000–2020). Major Taxa Studied Avian aerial insectivores. Methods We conducted a spatially explicit time‐window analysis to examine the effects of 17 gridded weather and vegetation variables on swallow peak roosting phenology in the Great Lakes, making minimal ecological assumptions. Results We found that peak roosting timing is paced by both local conditions (headwind at 850 hPa) at the Great Lakes and distant conditions (minimum temperature, precipitation rate and specific humidity) at the likely breeding and stopover sites, with warmer temperatures advancing, headwind delaying and high precipitation advancing the phenophases. Time windows selected for the possible breeding and stopover sites are mostly before or around the time of roosting, with one exception during wintertime. Main Conclusions Although climatic shifts play a significant role in driving variation in phenology, for migratory species, the proximate driver can originate hundreds to thousands of kilometres away, and potentially months prior. Our study illuminates these far‐reaching patterns in aerial insectivores, enhancing our grasp of migration ecology and paving the way for a more comprehensive understanding of hemispheric animal movements.

A machine learning classification of meteorite spectra applied to understanding asteroids - M. Darby Dyar; Sydney M. Wallace; Thomas H. Burbine; Daniel R. Sheldon (Icarus, 2023)

The impact of auditory distraction on learning and task performance in working dogs - Elizabeth L. Sheldon; Carla J. Hart; Daniel S. Mills; Carl D. Soulsbury; Rebecca Sumner; Anna Wilkinson (Applied Animal Behaviour Science, 2023)

Neutralizing Antibody Validation Testing and Reporting Harmonization - Heather Myler; João Pedras-Vasconcelos; Todd Lester; Francesca Civoli; Weifeng Xu; Bonnie Wu; Inna Vainshtein; Linlin Luo; Mohamed Hassanein; Susana Liu; Swarna Suba Ramaswamy; Johanna Mora; et al. (The AAPS Journal, 2023)
Evolving immunogenicity assay performance expectations and a lack of harmonized neutralizing antibody validation testing and reporting tools have resulted in significant time spent by health authorities and sponsors on resolving filing queries. A team of experts within the American Association of Pharmaceutical Scientists’ Therapeutic Product Immunogenicity Community across industry and the Food and Drug Administration addressed challenges unique to cell-based and non-cell-based neutralizing antibody assays. Harmonization of validation expectations and data reporting will facilitate filings to health authorities and are described in this manuscript. This team provides validation testing and reporting strategies and tools for the following assessments: (1) format selection; (2) cut point; (3) assay acceptance criteria; (4) control precision; (5) sensitivity including positive control selection and performance tracking; (6) negative control selection; (7) selectivity/specificity including matrix interference, hemolysis, lipemia, bilirubin, concomitant medications, and structurally similar analytes; (8) drug tolerance; (9) target tolerance; (10) sample stability; and (11) assay robustness. Graphical Abstract

Quantifying long‐term phenological patterns of aerial insectivores roosting in the Great Lakes region using weather surveillance radar - Yuting Deng; Maria Carolina T. D. Belotti; Wenlong Zhao; Zezhou Cheng; Gustavo Perez; Elske Tielens; Victoria F. Simons; Daniel R. Sheldon; Subhransu Maji; Jeffrey F. Kelly; Kyle G. Horton (Global Change Biology, 2023)
Organisms have been shifting their timing of life history events (phenology) in response to changes in the emergence of resources induced by climate change. Yet understanding these patterns at large scales and across long time series is often challenging. Here we used the US weather surveillance radar network to collect data on the timing of communal swallow and martin roosts and evaluate the scale of phenological shifts and its potential association with temperature. The discrete morning departures of these aggregated aerial insectivores from ground‐based roosting locations are detected by radars around sunrise. For the first time, we applied a machine learning algorithm to automatically detect and track these large‐scale behaviors. We used 21 years of data from 12 weather surveillance radar stations in the Great Lakes region to quantify the phenology in roosting behavior of aerial insectivores at three spatial levels: local roost cluster, radar station, and across the Great Lakes region. We show that their peak roosting activity timing has advanced by 2.26 days per decade at the regional scale. Similar signals of advancement were found at the station scale, but not at the local roost cluster scale. Air temperature trends in the Great Lakes region during the active roosting period were predictive of later stages of roosting phenology trends (75% and 90% passage dates). Our study represents one of the longest‐term broad‐scale phenology examinations of avian aerial insectivore species responding to environmental change and provides a stepping stone for examining potential phenological mismatches across trophic levels at broad spatial scales.

Near‐term ecological forecasting for dynamic aeroconservation of migratory birds - Kyle G. Horton; Benjamin M. Van Doren; Heidi J. Albers; Andrew Farnsworth; Daniel Sheldon (Conservation Biology, 2021)
Near‐term ecological forecasting has the potential to mitigate negative impacts of human modifications on wildlife by directing efficient action through relevant and timely predictions. We used the U.S. avian migration system to highlight ecological forecasting applications for aeroconservation. We used millions of observations from 143 weather surveillance radars to construct and evaluate a migration forecasting system for nocturnal bird migration over the contiguous United States. We identified the number of nights of mitigation required to reduce the risk of aerial hazards to 50% of avian migrants passing a given area in spring and autumn based on dynamic forecasts of migration activity. We also investigated an alternative approach, that is, employing a fixed conservation strategy based on time windows that historically capture 50% of migratory passage. In practice, during both spring and autumn, dynamic forecasts required fewer action nights compared with fixed window selection at all locations (spring: mean of 7.3 more alert days; fall: mean of 12.8 more alert days). This pattern resulted in part from the pulsed nature of bird migration captured in the radar data, where the majority (54.3%) of birds move on 10% of a migration season's nights. Our results highlight the benefits of near‐term ecological forecasting and the potential advantages of dynamic mitigation strategies over static ones, especially in the face of increasing risks to migrating birds from light pollution, wind energy infrastructure, and collisions with structures.

Climate‐driven range shifts of montane species vary with elevation - Margaret A. Mamantov; Daniel K. Gibson‐Reinemer; Ethan B. Linck; Kimberly S. Sheldon (Global Ecology and Biogeography, 2021)
Aim In response to warming, species are shifting their ranges towards higher elevations. These elevational range shifts have been documented in a variety of taxonomic groups across latitude. However, the rate and direction of species range shifts in response to warming vary, potentially as a consequence of variation in species traits across elevation. Specifically, diurnal and seasonal climates are often more variable at higher elevations, which results in high‐elevation species that have broader thermal physiologies relative to low‐elevation species. High‐elevation species that are thermal generalists might not need to move as far to track their thermal niche as low‐elevation thermal specialists. We investigated whether rates of range shifts varied systematically with increasing elevation across taxa and regions. Location Sixteen montane regions world‐wide. Time period 1850–2013. Taxon Nine hundred and eighty‐seven species of plants and animals. Methods We gathered published data on elevational range shifts from 20 transect studies comparing historical and recent distributions and examined how rates of range shifts changed across elevation. Specifically, we performed a meta‐analysis to calculate the pooled effect of elevation on species range shifts. Results We found that rates of range shifts show a negative relationship with elevation such that low‐elevation species have moved upslope farther than high‐elevation species on the same transect. This finding was primarily a result of shifts in the upper range limits. We also found that 28% of species shifted downslope against predictions, but elevation did not show a relationship with downslope range shifts. Main conclusions Idiosyncratic range shifts will significantly alter montane ecological communities, which are home to some of the greatest biodiversity on Earth. Our results demonstrate that species range shifts vary with elevation and might be a consequence of differences in species traits that also vary along montane gradients.

A place to land: spatiotemporal drivers of stopover habitat use by migrating birds - Emily B. Cohen; Kyle G. Horton; Peter P. Marra; Hannah L. Clipp; Andrew Farnsworth; Jaclyn A. Smolinsky; Daniel Sheldon; Jeffrey J. Buler (Ecology Letters, 2021)
Migrating birds require en route habitats to rest and refuel. Yet, habitat use has never been integrated with passage to understand the factors that determine where and when birds stopover during spring and autumn migration. Here, we introduce the stopover‐to‐passage ratio (SPR), the percentage of passage migrants that stop in an area, and use 8 years of data from 12 weather surveillance radars to estimate over 50% SPR during spring and autumn through the Gulf of Mexico and Atlantic coasts of the south‐eastern US, the most prominent corridor for North America’s migratory birds. During stopovers, birds concentrated close to the coast during spring and inland in forested landscapes during autumn, suggesting seasonal differences in habitat function and highlighting the vital role of stopover habitats in sustaining migratory communities. Beyond advancing understanding of migration ecology, SPR will facilitate conservation through identification of sites that are disproportionally selected for stopover by migrating birds.

Navigating north: how body mass and winds shape avian flight behaviours across a North American migratory flyway - Kyle G. Horton; Benjamin M. Van Doren; Frank A. La Sorte; Daniel Fink; Daniel Sheldon; Andrew Farnsworth; Jeffrey F. Kelly (Ecology Letters, 2018)
The migratory patterns of birds have been the focus of ecologists for millennia. What behavioural traits underlie these remarkably consistent movements? Addressing this question is central to advancing our understanding of migratory flight strategies and requires the integration of information across levels of biological organisation, e.g. species to communities. Here, we combine species‐specific observations from the eB ird citizen‐science database with observations aggregated from weather surveillance radars during spring migration in central North America. Our results confirm a core prediction of migration theory at an unprecedented national scale: body mass predicts variation in flight strategies across latitudes, with larger‐bodied species flying faster and compensating more for wind drift. We also find evidence that migrants travelling northward earlier in the spring increasingly compensate for wind drift at higher latitudes. This integration of information across biological scales provides new insight into patterns and determinants of broad‐scale flight strategies of migratory birds.

Multi‐century stasis in C 3 and C 4 grass distributions across the contiguous United States since the industrial revolution - Daniel M. Griffith; Jennifer M. Cotton; Rebecca L. Powell; Nathan D. Sheldon; Christopher J. Still (Journal of Biogeography, 2017)
Aims Understanding the functional response of ecosystems to past global change is crucial to predicting performance in future environments. One sensitive and functionally significant attribute of grassland ecosystems is the percentage of species that use the C 4 versus C 3 photosynthetic pathway. Grasses using C 3 and C 4 pathways are expected to have different responses to many aspects of anthropogenic environmental change that have followed the industrial revolution, including increases in temperature and atmospheric CO 2 , changes to land management and fire regimes, precipitation seasonality, and nitrogen deposition. In spite of dramatic environmental changes over the past 300 years, it is unknown if the C 4 grass percentage in grasslands has shifted. Location Contiguous United States of America. Methods Here, we used stable carbon isotope data (i.e. δ 13 C) from 30 years of soil samples, as well as herbivore tissues that date to 1739 CE , to reconstruct coarse‐grain C 3 and C 4 grass composition in North American grassland sites to compare with modern vegetation. We spatially resampled these three datasets to a shared 100‐km grid, allowing comparison of δ 13 C values at a resolution and extent common for climate model outputs and biogeographical studies. Results At this spatial grain, the bison tissue proxy was superior to the soil proxy because the soils reflect integration of local carbon inputs, whereas bison sample vegetation across landscapes. Bison isotope values indicate that historical grassland photosynthetic‐type composition was similar to modern vegetation. Main conclusions Despite major environmental change, comparing modern plot vegetation data to three centuries of bison δ 13 C data revealed that the biogeographical distribution of C 3 and C 4 grasses has not changed significantly since the 1700s. This is particularly surprising given the expected CO 2 fertilization of C 3 grasses. Our findings highlight the critical importance of capturing the full range of physiological, ecological and demographical processes in biosphere models predicting future climates and ecosystems.

Groundwater cooling of a supercomputer in Perth, Western Australia: hydrogeological simulations and thermal sustainability - Heather A. Sheldon; Peter M. Schaubs; Praveen K. Rachakonda; Michael G. Trefry; Lynn B. Reid; Daniel R. Lester; Guy Metcalfe; Thomas Poulet; Klaus Regenauer-Lieb (Hydrogeology Journal, 2015)

Elevated summer temperatures delay spawning and reduce redd construction for resident brook trout ( S alvelinus fontinalis ) - Dana R. Warren; Jason M. Robinson; Daniel C. Josephson; Daniel R. Sheldon; Clifford E. Kraft (Global Change Biology, 2012)
Redd (nest) surveys for resident brook trout ( S alvelinus fontinalis ) were conducted annually in a mountain lake in northern New York for 11 years with multiple surveys conducted during the spawning season in eight of those years. Repeated surveys throughout the spawning season allowed us to fit an individually based parametric model and estimate the day of year on which spawning was initiated, reached its midpoint, and ended during each year. Spawning phenology was then assessed relative to (1) mean of maximum daily air temperature and (2) mean of maximum daily water temperature at the lake bottom during summer in each year using a linear model. Elevated temperatures in summer were correlated with a delay in spawning and a reduction in the total number of redds constructed. Increasing the summer mean of maximum daily air temperatures by 1 °C delayed spawning by approximately 1 week and decreased the total number of redds constructed by nearly 65. Lake spawning brook trout select redd sites based on the presence of discharging groundwater that is relatively constant in temperature within and across years, leading to relatively consistent egg incubation times. Therefore, delayed spawning is likely to delay fry emergence, which could influence emergence synchrony with prey items. This work highlights non‐lethal and sub‐lethal effects of elevated summer temperatures on native resident salmonids in aquatic environments with limited thermal refugia.

Microvascular Thermal Equilibration in Rat Spinotrapezius Muscle - Ji Song; Lisa X. Xu; Daniel E. Lemons; Sheldon Weinbaum (Annals of Biomedical Engineering, 1999)

Microvascular thermal equilibration in rat cremaster muscle - Liang Zhu; Daniel E. Lemons; Sheldon Weinbaum (Annals of Biomedical Engineering, 1995)

A new approach for predicting the enhancement in the effective conductivity of perfused muscle tissue due to hyperthermia - Liang Zhu; Daniel E. Lemons; Sheldon Weinbaum (Annals of Biomedical Engineering, 1995)